Heretical Dimensions of Self Responsability by Jan Patočka - Tusa Ilea, Laura (Investigaciones Fenomenológicas, 2014)
Jan Patočka’s account of responsibility, as developed in Heretical Essays in the Philosophy of History, is configured through the philosopher’s entire model of history, seen less as a scale of progress, but rather as a rupture. Responsibility is possible only for a very specific form of humanity, centered on history, problematicity and selfdisclosure. This type of historic humanity is in profound contrast with the prehistoric one, focused on “daimonic participation.” Responsibility involves the passage from prehistory to history. Despite the fact that it requires an intense “discipline of the soul,” the passage to responsibility cannot become pure and transparent, which in turn means that history is repeatedly threatened by falling back into prehistory. The positive involved in this assumption is that responsibility is not taken for granted; it is not a matter of following metaphysical principles, but rather a matter of a practical, “heretical” decision of embracing history, with its shaken problematicity, and of resisting the temptation of prehistory. La comprensión de Jan Patočka de la responsabilidad, tal como se desarrolladen Ensayos eréticos de filosofía de la Historia, viene configurada por el modelo completo de Historia, vista más como una ruptura que como una escala de progreso. La responsabilidad es posible sólo para una forma muy concreta de humanidad, centrada en la historia, la problematicidad y el autodescubrimiento. Este tipo de humanidad histórica se halla en profundo contraste con el tipo prehistórico, focalizado sobre la “participación demónica”. La responsabilidad implica el tránsito de la prehistoria a la historia. Pese a requerir una intensa “disciplina del alma”, el tránsito a la responsabilidad no puede tornarse puro y transparente, lo que a su vez significa que la historia está constantemente amenzada por una recaída en la prehistoria. El lado positivo que esta asunción envuelve es que la responsabilidad no se da por garantizada; no es una cuestión de seguir principios metafísicos, sino más bien cuestión de una decisión práctica, “herética”, de abrazar la historia, con su problematicidad conmovida, y de resistir la tentación de la prehistoria.